Cr3+ and Cr4+ luminescence in glass ceramic silica - Martines, Marco A. U. [UNESP]; Davolos, Marian Rosaly [UNESP]; Jafelicci, Miguel [UNESP]; de Souza, Dione F.; Nunes, Luiz A. O. (Elsevier B.V., 2008)
This paper reports on the effect of glass ceramic silica matrix on [CrO4](4-) and Cr2O3 NIR and visible luminescence. Chromium-containing silica was obtained by precipitation from water-glass and chromium nitrate acid solution with thermal treatment at 1000 degrees C. From XRD results silica and silica-chromium samples are crystalline. The chromium emission spectrum presents two main broad bands: one in the NIR region (1.1-1.7 mu m) and other in the visible region (0.6-0.7 mu m) assigned to Cr4+ and to Cr3+, respectively. This thermal treated glass ceramic silica-chromium sample stabilizes the [CrO4](4-) where Cr4+ substitutes for Si4+ and also hexacoordinated Cr3+ group probably as segregated phase in the system. It can be pointed out that luminescence spectroscopy is a powerful toot for detecting the two chromium optical centers in the glass ceramic silica. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: silica; Chromium(III) and (IV); VIS and NIR luminescence